PLANT RESOURCE AND UTILIZATION: A CASE STUDY IN KANCHANPUR DISTRICT, FAR-WESTERN TARAI, NEPAL - Pant, Gunanand; Yadav, Ram Kailash P. (Ecoprint: An International Journal of Ecology, 2014)
The present study aims to explore and document the plant resources used by different communities ofSuda and Daijee VDC of Kanchanpur district. A total of 151 plant species belonging to 58 familiesand 133 genera have been identified and documented. Most of them have medicinal properties intheir bark, root, and fruits. A large number of these identified species are used for gastro-intestinalproblems, rheumatism, chest infection, cut and wound and in fever. Elderly people and traditionalhealers of the areas have vast knowledge on ethanomedicinal practices along with various rituals incomparison to the young generation. The knowledge transformation system is quite restricted withinfamily. Mostly exploited plant species like Piper longum, Emblica officinalis, Asparagus racemosus,Terminallia chebula, Terminalia bellirica, Acorus calamus, Azadirchta indica, Cordia vestita,Rauvolfia serpentina, Acacia catechu, Cinnamomum tamala, Zinziber officinalis, and Pterocarpusmarsupium are under threat of extinction due to growing human pressure as well as habitatdegradation impacted by anthropogenic activities such as grazing, expansion of agriculture land,forest fire, etc. DOI: http://dx.doi.org/10.3126/eco.v20i0.11470 ECOPRINT An International Journal of Ecology Vol. 20, 2013 page: 89-95